Fast track to health — Intermittent energy restriction in adolescents with obesity. A randomised controlled trial study protocol. Issue 1 (January 2020) - Lister, Natalie B.; Jebeile, Hiba; Truby, Helen; Garnett, Sarah P.; Varady, Krista A.; Cowell, Christopher T.; Collins, Clare E.; Paxton, Susan J.; Gow, Megan L.; Brown, Justin; Alexander, Shirley; Chisholm, Kerryn; et al.
Abstract: Background: Intermittent energy restriction (IER) has shown early success in adolescents with obesity, however efficacy trials are needed. This study aims to determine if IER results in lower body mass index (BMI) z-score after 52 weeks in metabolically unhealthy adolescents with obesity compared with continuous energy restriction (CER). Methods/design: This is a prospective, randomised, multi-centre trial conducted in tertiary care settings, with three phases: jumpstart (weeks 0–4); intensive intervention (weeks 5–16); continued intervention and/or maintenance (weeks 17–52). During the jumpstart phase, all participants follow a very low energy diet (∼800 kcal/3350 kJ/day), then transition to their allocated intervention: IER or CER. IER involves three energy-restricted days/week, consuming one-third of daily energy requirements (∼600−700 kcal/2500−2950 kJ/day), and four days/week of a healthy meal plan. The CER, which is current standard care, has individually tailored energy prescription based on age and sex (13–14 years, 1430−1670 kcal/6000−7000 kJ/day; 15–17 years, 1670−1900 kcal/7000−8000 kJ/day). The study will recruit 186 (93 per arm) treatment-seeking adolescents aged 13–17 years with obesity and at least one metabolic co-morbidity. The primary outcome is change in BMI z-score at 52 weeks. Secondary outcomes are changes at 4, 16 and 52 weeks in: body composition; diet quality, food choices and food patterns; cardio-metabolic risk factors; physical activity and sedentary behaviour; sleep and psycho-behavioural measures. Discussion: This study challenges existing clinical paradigms that CER is the only method for weight management in metabolically unhealthy adolescents. If successful, IER may offer an alternate medical nutrition therapy approach for those seeking treatment in tertiary settings. Clinical trial registration number: ACTRN12617001630303.